Wave sensitivity analysis for periodic and arbitrarily complex composite structures - Chronopoulos, Dimitrios; Collet, Manuel; Ichchou, Mohamed (Emerald, 2017)
Purpose: This paper presents the development of a numerical continuum-discrete approach for computing the sensitivity of the waves propagating in periodic composite structures. The work can be directly employed for evaluating the sensitivity of the structural dynamic performance with respect to geometric and layering structural modifications. Design/methodology/approach: A structure of arbitrary layering and geometric complexity is modelled using solid FE. A generic expression for computing the variation of the mass and the stiffness matrices of the structure with respect to the material and geometric characteristics is hereby given. The sensitivity of the structural wave properties can thus be numerically determined by computing the variability of the corresponding eigenvalues for the resulting eigenproblem. The exhibited approach is validated against the FD method as well as analytical results. Findings: An intense wavenumber dependence is observed for the sensitivity results of the sandwich structure. This exhibits the importance and potential of the presented tool with regard to the optimization of layered structures for specific applications. The model can also be used for computing the effect of the inclusion of smart layers such as auxetics and piezoelectrics. Originality/value: The paper presents the first continuum-discrete approach specifically developed for accurately and efficiently computing the sensitivity of the wave propagation data for periodic composite structures irrespective of their size. The considered structure can be of arbitrary layering and material characteristics as FE modelling is employed.